2020
DOI: 10.3390/pharmacy8020080
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Delivered in the Community Pharmacy to Manage Allergic Rhinitis- A Systematic Review of the Literature

Abstract: Pharmacists have a valuable role in the management of allergic rhinitis (AR) at the community pharmacy level. This role has been reported extensively in numerous papers. However, a systematic review of the available literature and a comprehensive analysis of the outcomes has not been published. This systematic review aimed to evaluate the impact of interventions developed by pharmacists on clinical AR outcomes. A thorough search was performed in three electronic databases, including studies published between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The features of the middle turbinate allow for more precise detection of the study population, monitoring of disease progression, and decision for medical treatment or surgical intervention. In contrast to previous similar studies, the lack of endoscopic features for disease progression and often limited patient-reported outcomes is addressed in this study [ 13 , 16 , 43 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The features of the middle turbinate allow for more precise detection of the study population, monitoring of disease progression, and decision for medical treatment or surgical intervention. In contrast to previous similar studies, the lack of endoscopic features for disease progression and often limited patient-reported outcomes is addressed in this study [ 13 , 16 , 43 ].…”
Section: Discussionmentioning
confidence: 97%
“…Only four studies were conducted between 2000 and 2020, focusing on educational interventions, mixed-method pharmacist versus patient-goal settings, and a case study observing the impact of pharmaceutical care [ 12 15 ]. Further research is needed to determine measurable outcomes in patients with allergic rhinitis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…"Pharmaceutical services" from pharmacists who have been trained in allergic rhinitis management improve patients' symptom control and quality of life. [ 12 ].…”
Section: Role Of Pharmacistsmentioning
confidence: 99%
“…The Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines have been used by health care professionals internationally for allergic rhinitis management [ 1 , 11 ]. A lack of knowledge of ARIA among pharmacists is observed as evidenced by insufficient counselling and treatment selection by pharmacists in allergic rhinitis management [ 12 ]. In a recent study, it was found that 40.4% of Malaysian pharmacists have inadequate awareness of the ARIA guidelines [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacist-led educational interventions improve patients' quality of life and symptom severity [ 14 ]. Pharmacists significantly influence patients' management of AR [ 15 , 16 ] by setting goals for care and providing pharmacist-led educational interventions [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%